2019
DOI: 10.1007/s00701-019-03973-7
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of patient-reported long-term outcomes following surgery for cauda equina syndrome

Abstract: Background Data regarding long-term outcomes following surgery for cauda equina syndrome (CES) is scarce. In addition, these studies rely on patient descriptions of the presence or absence of symptoms, with no gradation of severity. This study aimed to assess long-term bladder, bowel, sexual and physical function using validated questionnaires in a CES cohort. Methods A pre-existing ethically approved database was used to identify patients who had undergone surgery for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Improvement at follow-up significantly depended on the presence of a complete vs. incomplete CES (63.6% improvement in complete CES vs. 93.8% in incomplete CES, p = 0.048) but not on the underlying entity causing the CES ( p = 0.101). The rate of clinical recovery and persistence of numbness is congruent with published literature, describing better results in patients suffering from incomplete CES compared with complete CES 10 . BMI was not significantly associated with the probability of neurological recovery (mean BMI in patients with complete recovery 26.8 vs. 28.4 kg/m 2 , p = 0.577); symptom duration differed but failed to reach statistical significance (mean symptom duration in patients with complete recovery 2.6 days vs. 7.8 days in patients without complete recovery, p = 0.086).…”
Section: Resultssupporting
confidence: 87%
“…Improvement at follow-up significantly depended on the presence of a complete vs. incomplete CES (63.6% improvement in complete CES vs. 93.8% in incomplete CES, p = 0.048) but not on the underlying entity causing the CES ( p = 0.101). The rate of clinical recovery and persistence of numbness is congruent with published literature, describing better results in patients suffering from incomplete CES compared with complete CES 10 . BMI was not significantly associated with the probability of neurological recovery (mean BMI in patients with complete recovery 26.8 vs. 28.4 kg/m 2 , p = 0.577); symptom duration differed but failed to reach statistical significance (mean symptom duration in patients with complete recovery 2.6 days vs. 7.8 days in patients without complete recovery, p = 0.086).…”
Section: Resultssupporting
confidence: 87%
“…Studies that have measured quality of life outcomes in CES illustrate high levels of chronic pain impacting physical and social functioning albeit with low sample sizes [17]. Indeed, a recent assessment of the long‐term post‐surgical outcomes found that over a quarter of patients were unable to return to full employment with significantly poorer physical outcomes overall compared with the population average [18]. This on‐going symptomatic burden is reflected in our broad self‐report measures illustrating a chronic impairment to quality of life across all groups, giving important insight into the persistent disability experienced by a proportion of post‐surgical CES patients.…”
Section: Discussionmentioning
confidence: 99%
“…We used our institutional database for patients with cauda equina syndrome, which has previously been described in both Hoeritzauer et al and Hazelwood et al [6,8]. The data regarding psychiatric co-morbidity was previously reported in the Hoeritzauer et al dataset, of which this patient group is a selected subgroup [8].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported bladder, bowel, sexual and physical function outcomes using validated questionnaires in a cohort of post-operative CES patients [6]. In this current study we examine mental health outcomes in this same cohort, which also represents a selected subgroup of the patients included in a previous study by Hoeritzauer et al [8].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation